Expression of a cloned Bacillus thuringiensis delta-endotoxin gene in Bacillus subtilis. - Calogero, S (1989)
The entire coding region of the Bacillus thurigiensis HD73 crystal protein gene was subcloned from plasmid pJWK20 into the integration vector pUG2-15. This plasmid expresses chloramphenicol resistance when integrated into the Bacillus subtilis chromosome in the outH locus near the recE region. The correct molecular organization of the integrated plasmid was verified by hybridization to Southern blots of chromosomal DNA digests. Production of the toxic crystal protein was monitored at different time points during the life cycle of B. subtilis. Toxicity assays against Anagasta (Ephestia) larvae, direct electron microscopy crystal detection, and immunoblotting assays proved that the expression of the gene in B. subtilis is time regulated and restricted mainly to the sporulation stage. RNase protection experiments defined the transcription initiation start point and the transcription timing. All tests were made in a strain containing one to three copies of the integrated plasmid and in a strain subjected to an amplification regimen.